2016
DOI: 10.1161/strokeaha.116.014010
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Transient Ischemic Attack in Auckland, New Zealand, in 2011 to 2012

Abstract: Background and Purpose-There have been few recent population-based studies reporting the incidence (first ever) and attack rates (incident and recurrent) of transient ischemic attack (TIA). Methods-The fourth Auckland Regional Community Stroke study (ARCOS IV) used multiple overlapping case ascertainment methods to identify all hospitalized and nonhospitalized cases of TIA that occurred in people ≥16 years of age usually resident in Auckland (population ≥16 years of age is 1.12 million), during the 12 months f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…Comparisons with previous studies are limited because of the paucity of available information, and variations in the population are used for age standardizations. Only a few population-based studies reported the incidence of TIA (first-ever event) during the 2000s, with rates (standardized to the 2013 European population) ranging from 17 to 73/100,000/year [2-6]. These results are consistent with our present study (age-standardized rate: 61/100,000/year), which covered a more recent period of ascertainment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Comparisons with previous studies are limited because of the paucity of available information, and variations in the population are used for age standardizations. Only a few population-based studies reported the incidence of TIA (first-ever event) during the 2000s, with rates (standardized to the 2013 European population) ranging from 17 to 73/100,000/year [2-6]. These results are consistent with our present study (age-standardized rate: 61/100,000/year), which covered a more recent period of ascertainment.…”
Section: Discussionsupporting
confidence: 91%
“…Although most studies restricted their analyses to first-ever TIA, a few reported data on recurrent events, but the definition of recurrence that was applied differed between studies. For example, in the Auckland study, recurrent TIA was defined as a TIA event that occurred 28 days after the index event [2]. With this definition, recurrent TIA accounted for 6.8% of patients overall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The annual incidence of tia in the UK is estimated at 0.51 per 1000 population, 3 0.80 in Spain, 4 0.37-1.1 in the United States (US) 5 and 0.40 in New Zealand. 6 accurate diagnosis is important, as the early identification and treatment of tia substantially reduces patients' risk of subsequent stroke and consequent disability and mortality. 7 additionally, in France, it was reported that early assessment and management of tia and minor stroke resulted in ~80% reduction of recurrent stroke at 3 months from initial tia.…”
mentioning
confidence: 99%
“…Stroke, which includes ischemic stroke and hemorrhagic stroke, is one of the fatal or disabling cerebral vascular diseases [1,2]. Ischemic stroke accounts for over 80% of the total incidences of stroke.…”
Section: Introductionmentioning
confidence: 99%